UPAYA MENINGKATKAN PEMBELAJARAN TEKNIK DASAR BOLA VOLI DENGAN PERMAINAN SERVIS DAN PASSING GAMES PADA SISWA KELAS V SD NEGERI BANGO 2 KABUPATEN DEMAK TAHUN AJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study to determine the increase in learning outcomes movement using basic volleyball game service and passing games in the fifth grade students of SD Negeri 2 Demak Bango. The implementation of classroom action research was conducted in two cycles where each cycle consists of four stages: planning, action, observation (observation), and reflection. Methods of data collection in this study using the method of documentation, observation, and questionnaires. Analysis of research data with descriptive analysis percentage. Based on the survey results revealed that the learning outcomes of basic motion run in cycle 1 in category by 34% and completed in 2 cycles increased to 92%, where the percentage increased by 58%. Overall values obtained for each aspect has increased. The conclusion of the study is through a service game and passing games can improve learning outcomes volleyball.